Promoting the use of fluoride mouthwash as a preventive measure for dental caries among students of SDN 03 Cempaka Putih Barat - Ardinansyah, Agus; Nosi, Nur Hidayati; Atmaji, Moch; Hatta, Ridhayani; Pramigi, Ufo (Community Empowerment, 2025)
This community service aimed to enhance students' understanding of proper dental care and introduce the use of fluoride mouthwash as a preventive measure against dental caries. The program targeted fifth and sixth-grade students at SDN 03 Cempaka Putih Barat, who were identified as being at high risk for tooth decay. Through a series of educational sessions and practical demonstrations, students were taught the correct way to use fluoride mouthwash and the recommended frequency for preventing dental damage. Following the sessions, each student received a sample of fluoride mouthwash for home use and was scheduled to use it regularly at school. An evaluation was conducted three months after the intervention to measure its effectiveness. The evaluation included assessing the students' knowledge of dental health, observing changes in their behavior regarding fluoride mouthwash use, and conducting dental and oral health check-ups. The results showed a significant improvement in the students' knowledge, with the percentage of students understanding the causes of caries and preventive measures, including the regular use of fluoride mouthwash, increasing from 63% to 81%. It is hoped that this activity will be sustained and have a lasting positive impact on the dental health of children at SDN 03 Cempaka Putih Barat.